2011
DOI: 10.1016/j.fertnstert.2011.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Reanalyzing the modified Ferriman-Gallwey score: is there a simpler method for assessing the extent of hirsutism?

Abstract: Objective To determine whether assessing the extent of terminal hair growth in a subset of the traditional 9 areas included in the modified Ferriman-Gallwey (mFG) score can serve as a simpler predictor of total body hirsutism when compared to the full scoring system, and to determine if this new model can accurately distinguish hirsute from non-hirsute women. Design Cross-sectional analysis Setting Two tertiary care academic referral centers. Patients 1951 patients presenting for symptoms of androgen exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 17 publications
0
34
1
Order By: Relevance
“…We assessed hirsutism with the simplified version of the Ferriman-Gallwey score, which uses a scale of 0–3 to assess the amount of hair on a woman’s chin, upper abdomen, and lower abdomen. Women with a summed score ≥3 were considered has having hirsutism as a previous study determined this cutoff be highly predictive (12). …”
Section: Methodsmentioning
confidence: 99%
“…We assessed hirsutism with the simplified version of the Ferriman-Gallwey score, which uses a scale of 0–3 to assess the amount of hair on a woman’s chin, upper abdomen, and lower abdomen. Women with a summed score ≥3 were considered has having hirsutism as a previous study determined this cutoff be highly predictive (12). …”
Section: Methodsmentioning
confidence: 99%
“…Progesterone levels were measured on the 21 st day of the cycle. Hirsutism was established by using the Ferriman-Gallwey score (≥7) (14). The BMI and hirsutism scores were assessed by a single investigator for all of the subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the results obtained using the instrument presented in this study proved better than those reported in other recent studies in which simplified tests have also been proposed. One of those studies tested only three areas (29), while another, which also evaluated three regions, used a cut-off point of R2 (8). As this latter study was conducted exclusively with Chinese patients, in whom the prevalence of hirsutism is extremely low compared with women in other countries, application of this instrument will probably be restricted to that population (8,15,18,30).…”
Section: The Performance Of the Testmentioning
confidence: 99%